High coke-resistance Pt/Mg1-xNixO catalyst for dry reforming of methane - Al-Doghachi, Faris A. J.; Islam, Aminul; Zainal, Zulkarnain; Saiman, Mohd Izham; Embong, Zaidi; Yap, Taufiq Yun Hin (Public Library of Science, 2016)
A highly active and stable nano structured Pt/Mg1-xNixO catalysts was developed by a simple co-precipitation method. The obtained Pt/Mg1-xNixO catalyst exhibited cubic structure nanocatalyst with a size of 50–80 nm and realized CH4 and CO2 conversions as high as 98% at 900°C with excellent stability in the dry reforming of methane. The characterization of catalyst was performed using various kinds of analytical techniques including XRD, BET, XRF, TPR-H2, TGA, TEM, FESEM, FT-IR, and XPS analyses. Characterization of spent catalyst further confirms that Pt/Mg1-xNixO catalyst has high coke-resistance for dry reforming. Thus, the catalyst demonstrated in this study, offers a promising catalyst for resolving the dilemma between dispersion and reducibility of supported metal, as well as activity and stability during high temperature reactions.